On December 20, 2023, Brent will stop offering office hours.

- Video Course
- Video Course Overview
- General GMAT Strategies - 7 videos (free)
- Data Sufficiency - 16 videos (free)
- Arithmetic - 38 videos
- Powers and Roots - 36 videos
- Algebra and Equation Solving - 73 videos
- Word Problems - 48 videos
- Geometry - 42 videos
- Integer Properties - 38 videos
- Statistics - 20 videos
- Counting - 27 videos
- Probability - 23 videos
- Analytical Writing Assessment - 5 videos (free)
- Reading Comprehension - 10 videos (free)
- Critical Reasoning - 38 videos
- Sentence Correction - 70 videos
- Integrated Reasoning - 17 videos

- Study Guide
- Blog
- Philosophy
- Office Hours
- Extras
- Prices

## Comment on

2 and 3 with Exponent 7## Why does it become 3*3 to the

## This is a general property of

This is a general property of all numbers.

Let's examine some similar examples:

8 + 8 + 8 = (3)(8)

1.1 + 1.1 + 1.1 = (3)(1.1)

20 + 20 + 20 = (3)(20)

x + x + x = 3x

k² + k² + k² = 3k²

Likewise, 3^7 + 3^7 + 3^7 = (3)(3^7)

Does that help?

## Okay I get it now. Thank you

## Great video. After viewing

## Why can’t it be (9^7)(4^7)? I

## You are suggesting that 3^7 +

You are suggesting that 3^7 + 3^7 + 3^7 = 9^7

So, you are adding the bases and keeping the exponents the same.

Unfortunately, this approach is not valid.

Let's examine some counter-examples that demonstrate that we can't just add the bases and keep the exponents the same:

1^5 + 1^5 + 1^5

Using your approach, we get: 1^5 + 1^5 + 1^5 = 3^5

Is this true?

No.

1^5 = 1

So, 1^5 + 1^5 + 1^5 = 1 + 1 + 1 = 3

However, your approach suggests that 1^5 + 1^5 + 1^5 = 3^5, yet 3^5 = 243

Or what about:

5^2 + 5^2

Using your approach, we get: 5^2 + 5^2 = 10^2

Is this true?

No.

5^2 = 25

So, 5^2 + 5^2 = 25 + 25 = 50

However, your approach suggests that 5^2 + 5^2 = 10^2 = 100

Does that help clear things up?

Cheers,

Brent

## That makes sense! Thanks! Now

Thanks again!

## Is there no other way of

## Unfortunately, there's no

Unfortunately, there's no better approach.

This questions tests a very important general property of all numbers, so let's go over the solution.

First, here are some similar examples:

8 + 8 + 8 = (3)(8)

1.1 + 1.1 + 1.1 = (3)(1.1)

20 + 20 + 20 = (3)(20)

x + x + x = 3x

5w + 5w + 5w = (3)(5w) = 15w

k² + k² + k² = 3k²

Likewise, 3^7 + 3^7 + 3^7 = (3)(3^7)

The same concept applies to 2^7

Does that help?

Cheers,

Brent

## Hi Brent,

Thank you for this video.

I have a slightly different approach, but I do not know if it's the right method

I factor out (3^7)(1+1+1) x (2^7)(1+1)

= (3^7)(3^1) x (2^7)(2^1)

= 3^8 x 2^8

= 6^8

Is my method valid?

## Yours is a perfectly valid

Yours is a perfectly valid approach.

In my approach, I collected like terms to get: 3^7 + 3^7 + 3^7 = (3)(3^7), in the same way that k + k + k = 3k.

In your approach, you took 3^7 + 3^7 + 3^7 and factored out a 3^7 to get: 3^7(1 + 1 + 1)

When we simplify 3^7(1 + 1 + 1), we get (3)(3^7)

So, both approaches allow us to simplify 3^7 + 3^7 + 3^7 to get (3)(3^7)

Cheers,

Brent